Fermi-level tuning of the Dirac surface state in (Bi1−xSbx)2Se3 thin films. (1st February 2018) - Satake, Yosuke; Shiogai, Junichi; Takane, Daichi; Yamada, Keiko; Fujiwara, Kohei; Souma, Seigo; Sato, Takafumi; Takahashi, Takashi; Tsukazaki, Atsushi
Abstract: We report on the electronic states and the transport properties of three-dimensional topological insulator (Bi1− x Sb x )2 Se3 ternary alloy thin films grown on an isostructural Bi2 Se3 buffer layer on InP substrates. By angle-resolved photoemission spectroscopy, we clearly detected Dirac surface states with a large bulk band gap of 0.2–0.3 eV in the (Bi1− x Sb x )2 Se3 film with x   =  0.70. In addition, we observed by Hall effect measurements that the dominant charge carrier converts from electron ( n -type) to hole ( p -type) at around x   =  0.7, indicating that the Fermi level can be controlled across the Dirac point. Indeed, the carrier transport was shown to be governed by Dirac surface state in 0.63  ⩽   x   ⩽  0.75. These features suggest that Fermi-level tunable (Bi1− x Sb x )2 Se3 -based heterostructures provide a platform for extracting exotic topological phenomena.